ANALISIS PEMAHAMAN MAHASISWA GENERASI Z TERHADAP TREN FASHION MUSLIMAH MODERN DITINJAU DARI PRINSIP SYARIAT ISLAM - Mutiara Zahara; Nurul Nadia; Sahru Ramadan; Syifa Eriza Nasution; Hapni Laila Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of digital technology and social media has brought significant changes to the Muslim fashion industry, particularly in how the younger generation perceives Muslimah attire. For Generation Z, Muslimah fashion is no longer seen merely as a religious obligation but has shifted into a lifestyle, an aesthetic trend, and an expression of self-identity. This study aims to analyze Generation Z female students' understanding of modern Muslimah fashion trends and assess their alignment with Islamic Sharia principles, including the indicators of covering the awrah, the prohibition of tabarruj (excessive adornment), and the principle of modesty. This research employs a qualitative approach with a descriptive method. Data were collected through open-ended questionnaires distributed to ten Muslimah students at the State University of Medan (UNIMED) via Google Forms. The data were analyzed using thematic analysis techniques to identify patterns in respondents' understanding of Islamic dress codes, their views on modern fashion trends, and the external factors influencing their personal style. The results indicate that most respondents have a relatively good understanding of the fundamental principles of dressing in Islam, particularly regarding the obligation to cover the awrah, the use of non-transparent materials, and avoiding overly tight clothing. However, the development of modern Muslimah fashion trends, heavily influenced by social media and popular culture, occasionally leads to fashion practices that do not fully comply with Sharia principles, such as imperfect hijab styles or looks that emphasize excessive ornamentation. Therefore, a balance between fashion aesthetics and religious values is necessary to ensure thatthe evolution of Muslimah attire remains aligned with the core principles of Islamic Sharia.